The ability to detect wild boars with increased body temperature in the natural environment with the use of unmanned aerial vehicles equipped with thermovision in two provinces in Poland - Wójcicka, P.; Żakowska, D.; Głowacka, P.; Adamczyk, P.; Graniak, G.; Rutyna, P.; Bijak, M.; Podogrocki, M.; Niemcewicz, M. (Polish Journal of Veterinary Sciences, 2026)
African swine fever (ASF) is a highly contagious disease affecting both free-living wild boars (Sus scrofa) and domestic pigs (Sus scrofa domesticus). In accordance with EU regulations, an ASF outbreak in pig farms necessitates immediate herd culling, leading to severe economic losses and restrictions on pork exports. Therefore, effective epidemiological surveillance of wild boar populations is crucial for monitoring the spread of the disease in the natural environment and preventing transmission to domestic pig farms. This study assessed the effectiveness of an ASF surveillance system consisting of the AtraxASF (unmanned aerial vehicle) and the NeoxASF (fixed-wing aircraft), both equipped with thermal imaging cameras. The study was conducted in Mielec County, Subcarpathian Province, an area with confirmed ASF outbreaks. The proposed surveillance system was used to observe wild boars and identify individuals exhibiting elevated body temperature, which is the earliest detectable symptom of ASF infection. The thermal imaging technology allowed for real-time detection and mapping of potentially infected animals. The system successfully detected wild boars with increased body temperature, demonstrating its potential utility for early detection of ASF in wildlife populations. The application of drone- and aircraft-based monitoring significantly enhanced surveillance efficiency by providing a rapid, non-invasive approach to assessing the health status of wild boar populations in affected areas. The implementation of drone-based surveillance systems and thermal imaging technologies offers a highly effective alternative to traditional epidemiological monitoring methods. The system enhances early detection capabilities, enabling quicker response measures to prevent the spread of ASF to pig farms. Integrating such technologies into existing biosecurity strategies could play a key role in controlling ASF outbreaks and minimizing economic losses in the pig farming sector.